Nefarious Presentism: A Recourse to Primitivism - Ajiboro, Aderonke (Conatus - Journal of Philosophy, 2020)
Presentism is one of the various views in the discourse on the existence of time and spatio-temporal reality which holds that only the present is real and also that only present things exist. Neil McKinnon characterizes presentism in some ways that are all problematic, although he claims that the most appealing of all is the statement that “only present entities exist.” This view permeates all thoughts about presentism, and it has led to problems about the formulation of presentism. The link between accepting the existence of a temporal part (present) and the events that have that part as its spatio-temporal reference creates a hub of debate among presentists, and this raises a lot of issues not just in metaphysics, but in other areas of philosophical discourse as well. Tallant and Ingram take a challenging position on this issue as presentists in their own right. For them, the requisite status of a presentist properly so-called should be of a commitment to the reality of the present exclusively. In this paper, I engage the views of Tallant and Ingram on the problems of presentism such as triviality and truthmaking as regards ontological implications. I will argue that the avoidance of ontological commitment in nefarious presentism does appear to avoid the problem of truthmaking, which implies avoiding an analysis of truth in order to solve the problem of truthmaking. I will also argue that this avoidance to address the principle of un-analyzability of thisness is a recourse to primitivism.